IMPROVEMENT IN QUALITY-OF-LIFE AND DEPRESSIVE SYMPTOMS DURING LONG-TERM TREATMENT WITH ESLICARBAZEPINE ACETATE: BIA-2093-301 STUDY. Issue 11 (9th October 2013) - Cramer, Joyce; Elger, C; Halasz, P; Hodoba, D; Czlonkowska, A; Maia, Joana; Almeida, L; Soares-da-Silva, P
Abstract : Rationale: To assess the improvement in quality-of-life and depressive symptoms during long-term adjunctive therapy with eslicarbazepine acetate (ESL) in patients with refractory partial epilepsy. Methods: During an open-label extension of a phase 3 study (BIA-2093-301) with ESL, the Quality-of-Life in Epilepsy Inventory 31 (QOLIE-31) and Montgomery Asberg Depression Rating Scale (MADRS) were applied at the end of the treatment period (1 year or early discontinuation) and the results were compared with those at baseline. Most patients were treated with ESL 800 mg once-daily (range: 400–1600 mg). Results: QOLIE-31 results in the intent-to-treat (ITT) population (n=255) showed significant improvements from baseline in overall quality of life (p<0.0001), seizure worry (p<0.0001), energy-fatigue (p<0.05), cognitive functioning (p<0.05), medication effects (p<0.0001), social function (p<0.01), and the overall score (p<0.0001). In the per-protocol (PP) population (n=224), significant improvements were found in all scores: overall quality-of-life (p<0.0001), seizure worry (p<0.0001), emotional well-being (p<0.01), energy-fatigue (p <0.001), cognitive functioning (p<0.01), medication effects (p<0.0001), in social function (p<0.001), and overall score (p<0.0001). MADRS results in the ITT population (n=265) also showed significant improvements in the total score (from 9.5 to 7.2; p<0.0001), apparent sadness (p=0.0001), inner tension (p<0.001), reported sadness (p<0.01), concentration difficulties (p<0.0001), lassitude (p<0.001), inability to feel (p<0.01), and pessimistic thoughts (p<0.05). In the PP population (n=232), significant improvements were found in the total score (p<0.0001), apparent sadness (p<0.0001), inner tension (p<0.0001), reported sadness (p<0.01), concentration difficulties (p<0.0001), lassitude (p<0.001), inability to feel (p<0.01), and pessimistic thoughts (p<0.01). Conclusions: Quality-of-life, as assessed by QOLIE-31, and depressive mood, as assessed by MADRS, showed statistically significant improvement from baseline during long-term open-label adjunctive therapy with ESL in partial epilepsy.